1992
DOI: 10.1111/j.1476-5381.1992.tb14306.x
|View full text |Cite
|
Sign up to set email alerts
|

Opposing roles for 5‐HT1B and 5‐HT3 receptors in the control of 5‐HT release in rat hippocampus in vivo

Abstract: 1 Intracerebral microdialysis was used to determine whether 5-hydroxytryptamine (5-HT) release in the ventral hippocampus of rats anaesthetized with chloral hydrate was modulated by 5-HT3 receptors. 2 It was confirmed that 5-methoxy-3-(1,2,3,6-tetrahydro-4-pyridinyl)-lH-indole (RU 24969), a selective 5-HTB receptor agonist, decreased 5-HT release in a dose-and concentration-related manner when administered i.p. (1 and 5 mg kg-') or via the dialysis probe (0.1 and 1 ftM) respectively. The effect of RU 24969 inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(52 citation statements)
references
References 26 publications
5
47
0
Order By: Relevance
“…The relative potency order of the antagonists observed in the present study relates fairly well to the data obtained in the guinea-pig vagus preparation (see Hoyer, 1990 (Ge et al, 1991;Martin et al, 1992). It is noteworthy that in the latter report, 2-methyl-5-HT enhanced the extracellular level of 5-HT, and this enhancing effect was prevented by MDL 72222 (Martin et al, 1992). However, given the capacity of this 5-HT3 receptor to desensitize rapidly and the markedly different quantitative effect it can exert over a very narrow range of 5-HT release, it would seem that microdialysis may not be ideally suited to study its influence on the modulation of 5-HT release in vivo.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The relative potency order of the antagonists observed in the present study relates fairly well to the data obtained in the guinea-pig vagus preparation (see Hoyer, 1990 (Ge et al, 1991;Martin et al, 1992). It is noteworthy that in the latter report, 2-methyl-5-HT enhanced the extracellular level of 5-HT, and this enhancing effect was prevented by MDL 72222 (Martin et al, 1992). However, given the capacity of this 5-HT3 receptor to desensitize rapidly and the markedly different quantitative effect it can exert over a very narrow range of 5-HT release, it would seem that microdialysis may not be ideally suited to study its influence on the modulation of 5-HT release in vivo.…”
Section: Discussionsupporting
confidence: 77%
“…Nethertheless, R-and S-zacopride were effective down to a concentration of 10 nM. The relative potency order of the antagonists observed in the present study relates fairly well to the data obtained in the guinea-pig vagus preparation (see Hoyer, 1990 (Ge et al, 1991;Martin et al, 1992). It is noteworthy that in the latter report, 2-methyl-5-HT enhanced the extracellular level of 5-HT, and this enhancing effect was prevented by MDL 72222 (Martin et al, 1992).…”
Section: Discussionsupporting
confidence: 77%
“…Later, it was reported that 5-HT suppresses long term potentiation (LTP) in hippocampal slices by preventing the activation of NMDA receptors and the enhancement of AMPA-mediated currents that lead to LTP induction [171]. The hippocampus contains several subtypes of serotonin receptors, namely 5-HT 1A [160,174], 5HT 1B [4,130], 5-HT 2 [17,28], 5-HT 3 [116,132], 5-HT 4 [5,160], 5-HT 6 and 5-HT 7 [73], many of which modulate glutamate-mediated transmission acting at different levels. In the CA1 region, pre-synaptic 5-HT 1A receptors reduce glutamate release from Schaffer collaterals to CA1 pyramidal neurons [162] (Fig.…”
Section: Modulation Of Glutamate Transmissionmentioning
confidence: 99%
“…In spite of this promising perspective, experiments to demonstrate 5-HT 3 receptor-mediated 5-HT release in the amygdala do not appear to have been carried out. By contrast, a 5-HT 3 receptor-mediated enhancement of 5-HT release has been reported from other brain regions, for example, hippocampus, frontal cortex, hypothalamus, and raphé nucleus [22][23][24][25] . However, the presence of 5-HT 3 receptors on serotonergic nerve endings in these brain regions has not been demonstrated thus far.…”
Section: -Ht Releasementioning
confidence: 92%